Leucine minimizes denervation-induced skeletal muscle atrophy of rats through akt/mtor signaling pathways - Ribeiro, Carolina B.; Christofoletti, Daiane C.; Pezolato, Vitor A.; de Cássia Marqueti Durigan, Rita; Prestes, Jonato; Tibana, Ramires A.; Pereira, Elaine C. L.; de Sousa Neto, Ivo V.; Durigan, João L. Q.; da Silva, Carlos A. (Frontiers in Physiology, 2015)
The aim of the present study was to evaluate the effect of leucine treatment (0.30 mM) on muscle weight and signaling of myoproteins related to synthesis and degradation pathways of soleus muscle following seven days of complete sciatic nerve lesion.Wistar rats (n=24) of 3 to 4 months of age (192 ± 23 g) were used. The animals were randomly distributed into four experimental groups (n=6/group): control, treated with leucine (L), denervated (D) and denervated treated with leucine (DL).Dependent measures were proteins levels of AKT, AMPK, mTOR, and ACC performed by Western blot. Leucine induced a reduction in the phosphorylation of AMPK (p<0.05) by 16% in the L and by 68% in the DL groups as compared with control group. Denervation increased AMPK by 24% in the D group as compared with the control group (p<0.05). AKT was also modulated by denervation and leucine treatment, highlighted by the elevation of AKT phosphorylation in the D (65%), L (98%) and DL (146%) groups as compared with the control group (p<0.05). AKT phosphorylation was 49% higher in the D group as compared with the DL group.Furthermore, denervation decreased mTOR phosphorylation by 29% in the D group as compared with the control group. However, leucine treatment induced an increase of 49% in the phosphorylation of mTOR in the L group as compared with the control group, and an increase of 154% in the DL as compared with the D group ( p<0.05). ACC phosphorylation was 20% greater in the D group than the control group. Furthermore, ACC in the soleus was 22% lower in the in the L group and 50% lower in the DL group than the respective control group (p<0.05).In conclusion, leucine treatment minimized the deleterious effects of denervation on rat soleus muscle by increasing anabolic (AKT and mTOR) and decreasing catabolic (AMPK) pathways. These results may be interesting for muscle recovery following acute denervation, which may contribute to musculoskeletal rehabilitation after denervation.